Revitalisasi Usaha Budidaya Lebah Kelulut di Desa Tanjung Sari Kabupaten Kepulauan Meranti, Provinsi Riau: Masalah dan Solusinya - Muhammad, Ahmad; Qomar, Nurul; Mahatma, Radith; Pranata, Syafroni (Journal of Community Engagement Research for Sustainability, 2022)
Meliponiculture emerged at Tanjung Sari, a village in Kepulauan Meranti Regency, Riau Province, in 2016 and has been growing thereafter. According to our observations there were at least three main obstacles faced by colony owners at this village, i.e. colony loss, low honey production, and marketing-related issues. We attempted to address these issues through a participatory program involving colony owners of the village. Colony loss had been mainly caused by swarming and mortality and was believed to have been triggered by inappropriate conditions of the maintenance (such as too much exposure to the sun and rain as well as unrepelled diturbances by other animals. Such conditions had also been associated with low honey production. Therefore we encouraged villagers to improve the conditions by providing supporter and roof for their colonies. In regard with marketing issues, we encouraged villagers to establish a honey cooperative under BUMDES, which should regulate honey price, absorb the produced honey, and also handle its marketing to outer counterparts. In addition, the cooperative should facilitate communications between members and information disemination, and mediate negotiation with potential buyers. The benefits gained by participants were: (1) the improvement of technical knowledge of colony maintenance; (2) the improvement of colony maintenance quality that would reduce risk of colony loss; and (3) the establishment of a cooperative that would be a body that would facilitate the necessities previously mentioned. The present paper describes the processes and results in details.